Susceptibility of immature Telenomus remus, an egg parasitoid of Spodoptera frugiperda (J.E. Smith), to entomopathogenic fungi from South Sumatra, Indonesia - Qarina Shafira Putri; Wenti Oktapiani; Siti Herlinda; Suwandi Suwandi (Egyptian Journal of Biological Pest Control, 2024)
Abstract Background The fall armyworm (FAW) Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is a newly introduced pest that damages maize production in Indonesia. To control this pest in maize fields, better solution is to use the egg parasitoid, such as Telenomus remus Nixon (Hymenoptera: Scelionidae), as another better option to apply topically entomopathogenic fungi (EPF). Therefore, it is necessary to study the effect of the EPF on the egg parasitoid of T. remus. The objective of this research was to evaluate susceptibility of immature T. remus to the EPFs, Beauveria bassiana, Chaetomium sp., Curvularia lunata, Penicillium citrinum, and Metarhizium anisopliae. The EPFs (1 × 106 conidia mL−1) were sprayed topically on one-day-old mummies (immature T. remus) in post-parasitism periods. Results The results showed that the cumulative percentage of T. remus adult emergence from the mummies treated with EPF on 11 days after treatment ranged 54–100% and was non-significantly different than those of control (untreated with EPF) (90.48%). Therefore, the immature stage of T. remus was not susceptible to the EPF topical application. The EPFs were harmless to the immature stage of T. remus. Percentage of aborted mummies (embryonic death) of T. remus after treated with the EPF was also non-significantly different than those of control. However, the EPFs could significantly affect developmental times of immatures stages of T. remus. The EPF also could shorten the adult longevity of the egg parasitoid. Conclusions The immature T. remus is less sensitive to the EPFs; B. bassiana, Chaetomium sp., C. lunata, P. citrinum, and M. anisopliae. It can be considered integrating the EPF with T. remus inundation in maize field. However, it is necessary to limit the topical application of the EPF to avoid negative effects on the adult longevity of the egg parasitoid. Thus, it needed to be further investigated that the application of the endophytic EPFs by inoculating the fungi within the plant tissue could be harmless to the egg parasitoids.